Review of Research Progress on Aluminum-Magnesium Dissimilar Friction Stir Welding - L. H., Shah; Nurul Hidayah, Othman; Gerlich, Adrian (Taylor & Francis Online, 2017)
The paper critically assesses the research progress towards aluminum-magnesium dissimilar friction stir welding (FSW). First, the theoretical requirements are explored through the understanding of joining mechanism and heat generation in aluminum-magnesium FSW. Next, the observed trends in microstructural characterization and mechanical properties are analyzed. Lastly, the effects of welding parameters and how it influences process variables and materials responses are discussed in detail, and several suggestions are made based on these discussions.